The Political Theology of J. B. Metz - Corral Salvador, Carlos (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
After the turbulent II World War, the World, but especially Europe, became divided into two blocks: the communist one and the liberal-western one, both in their ideas and their geography and borders. This partition was to affect also the religions, particularly the Christian churches, with special effect in the Catholic Church, because of its characteristics of universality and unity. This was also the case of the theology and its authors. This makes necessary to contextualize the Political Theology of Metz within the framework of that theology and that history.
Keywords: Political Theology; Fundamental Theology; Eschatology; Secularism; Marxism